Blister Fluid Induces MMP-9-Associated M2-Type Macrophages in Bullous Pemphigoid - Riani, Meriem; Muller, Céline; Bour, Camille; Bernard, Philippe; Antonicelli, Frank; Le Jan, Sébastien (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) is a cutaneous autoimmune disease, characterized by an inflammatory cascade leading to blister formation. Although macrophages were shown to participate in BP pathophysiology, their role in the blister formation process still needs to be investigated. We here addressed the influence of serum and blister fluid (BF) from patients with BP on the polarization status of macrophages with regards to the metalloproteinase-9 (MMP-9) expression. We demonstrated that several markers related to the alternatively activated macrophage phenotype (M2) including IL-10, TARC, arginase, TNFα and IL-1RA were meaningfully increased in BF of patients with BP. We further showed that BF, but not serum from patients with BP, significantly induced the expression of CD163, CD206 and IL-10 in BP monocyte-derived macrophages. Notably IL-10 was the only cytokine to be correlated to the reference clinical score, BP disease activity index (BPDAI), especially to the inflammatory BPDAI subscore evaluating urticarial and erythematous skin lesions (r=0.57, p=0.0004). We also found elevated levels of MMP-9 to M2-type macrophages ex vivo and highlighted the presence of CD163+ MMP-9+ macrophages histologically, at skin lesional site. Finally, we showed that methylprednisolone reduced MMP-9 levels in monocyte-derived macrophages without modifying the other M2 markers. All together these results strongly support the presence of M2-phenotype macrophages with pro-inflammatory properties susceptible to favour blister formation in BP.